EU enlargement and environmental policy - Andreas Löschel; Marian Mraz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The Eastern European Associates (EEA) have committed to reduce greenhouse gas emissions according to their targets set in the Kyoto Protocol. Furthermore since 1993 trade liberalization has taken place between all associated countries and the EU. There is meanwhile a large quantitative literature on the economic effects of full integration of the associated countries into the EU as well as on the Kyoto Protocol. However, there is a lack of quantitative research on the linkage of trade and the environment in the context of the EU enlargement. In this paper we analyze the interactions of different environmental policies under the Kyoto Protocol and trade liberalization in the process of eastern enlargement using a computable general equilibrium model. We find that trade liberalization provides large gains for EEAs while it holds only modest gains for EU member states. Integration does not show a significant impact on carbon abatement policies, but mitigates associated welfare losses.
Keywords: Q25; F15; P20; F18; D58; 330; EU enlargement; Kyoto Protocol; computable general equilibrium modeling; Klimaschutz; EU-Erweiterung; Außenhandelsliberalisierung; Luftverunreinigung; Kohlendioxid; Umweltschutzkosten; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Osteuropa; EU-Staaten